Ethnicity-based classifications and medical genetics: One Health approaches from a Western Pacific perspective - Edinur, Hisham A.; Mat-Ghani, Siti Nor A.; Chambers, Geoffrey K. (Frontiers in Genetics, 2022)
A new era presently dawns for medical genetics featuring individualised whole genome sequencing and promising personalised medical genetics. Accordingly, we direct readers attention to the continuing value of allele frequency data from Genome-Wide Association Surveys (GWAS) and single gene surveys in well-defined ethnic populations as a guide for best practice in diagnosis, therapy and prescription. Supporting evidence is drawn from our experiences working with Austronesian volunteer subjects across the Western Pacific. In general, these studies show that their gene pool has been shaped by natural selection and become highly diverged from those of Europeans and Asians. These uniquely evolved patterns of genetic variation underlie contrasting schedules of disease incidence and drug response. Thus, recognition of historical bonds of kinship among Austronesian population groups across the Asia Pacific has distinct public health advantages from a One Health perspective. Other than diseases that are common among them like gout and diabetes, Austronesian populations face a wide range of climate-dependent infectious diseases including vector-borne pathogens as they are now scattered across the Pacific and Indian Oceans. However, we caution that the value of genetic survey data in Austronesians (and other groups too) is critically dependent on the accuracy of attached descriptive information in associated metadata, including ethnicity and admixture.